Colonic Crohn Disease - Hedrick, Traci L.; Friel, Charles M. (Clinics in Colon and Rectal Surgery, 2013)
Colonic Crohn disease is a complicated disease entity that requires a multidisciplinary effort on the part of the surgeon, gastroenterologist, and pathologist. Crohn disease affects ∼500,000 people in North America with nearly 300,000 people suffering from colonic manifestations. This represents a significant portion of the patient population in the typical colorectal surgeon's practice. As such, an intimate understanding of the disease process, presentation, and treatment options is imperative. In this article, the authors review the clinical manifestations, diagnosis, and medical and surgical treatment options with a focus on current strategies for surgical management.
Keywords: Crohn disease; colitis; surgical management